The Role of Gender in the Relation Among Anxiety, Theory of Mind, and Well-Being in Early Adolescents. (August 2023) - Caputi, Marcella; Bosacki, Sandra
The relation between cognition and life satisfaction is shaped by several factors. The present research investigated whether mindreading skills are linked to subjective well-being and anxiety during the transition into adolescence. Specifically, our aim was to investigate individual differences in those constructs and gendered relational patterns. A sample of 142 Italian sixth- and seventh-graders (84 boys, M = 11.83 years, SD = 6.87 months) completed a theory-of-mind task, and questionnaires on perceptions of different anxiety subtypes and life satisfaction. In the total sample, no interrelations were found among the variables. Nonetheless, mediation analyses conducted separately by gender showed that, only among girls, higher theory-of-mind scores were associated with lower perception of life satisfaction through the mediation of higher generalized anxiety levels. Results suggest that the approach to adolescence may provide a timely intervention window to develop preventive programs that target internalizing symptoms and their cascade effects on young people's well-being.